ECE643: Fundamentals Of Network Security / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
This course covers basic principle of core security technologies and infrastructure. This is achieved by recognizing vulnerabilities to networks and mitigates potential security threats including intrusion prevention system and traffic filtering. The network security aspects such as computer virus, firewall and establish security policy are also considered.